The Role of Touristic Product Components in Destination Selection - GORAL, Ramazan; AKGOZ, Erkan; KAPUSUZ, Ayse GOKCEN; YURTLU, Murat (Journal of Tourism Management Research, 2022)
This research analyzed the effect of the main touristic product components (Cultural and Natural Attractions, Tourism Services Infrastructure, Transportation Facilities, Price Accessibility, and Image) on tourists’ destination selection in the seven most-visited destinations in the world in 2020 (France, Spain, the USA, China, Italy, Turkey, and Mexico). The selected destinations were analyzed and compared with the PROMETHEE technique, using the data in the 2019 reports of the “Travel and Tourism Competitiveness Index” and the "Tourism Brand Country Ranking." The results of the analysis showed the order of superiority of the destinations as Spain, France, Italy, China, the USA, Mexico, and Turkey. The criteria and effect levels that affected this ranking are examined in detail for each destination in the findings section of this paper. It was concluded that Turkey fell behind in the ranking due, in particular, to its low performance in the Cultural and Natural Attractiveness category, despite its rich cultural and natural values. This research reveals that differences in the ranking of the 7 countries that attract the most tourists in the world depend on the characteristics of the various touristic product components, and the reasons for these differences are within the touristic product components framework.